A Training Program Based on Digital Morphology To Acquire The Skill of Scenographic Formation For (Journal of the College of Basic Education, 2024)
The study aimed to build a training program according to digital morphology and to identify the impact of the program in acquiring the skill of synoptic formation among technical supervisors. To achieve this goal, the researcher developed the following hypothesis: There are no statistically significant differences between the average grades of the experimental group members in the tribal and post-test applications of the skill test of synoptic formation. The current research was limited to the technical supervisors in the theater unit/ Directorate of Karkh Education first, in the province of Baghdad (2022-2023). To achieve the objectives of the research, the experimental design was used with experimental and control groups with tribal and post-test, and the research sample consisted of (16) technical supervisor divided into two groups that were equivalent in the variables of age, sex, years of service, theatrical experience. The skill of the synoptic formation was measured based on the skill test of the synoptic formation prepared by the researcher, and to achieve the goal of the research, the researcher prepared a training program according to digital morphology, and the program consisted of (8) sessions of two sessions per week, the duration of each session ranging from (90-120) minutes, and the research required the use of appropriate statistical means. After the completion of the application of the program, the result of the research that there are statistically significant differences between the average grades of the experimental group and the control of the skill test of the synoptic formation in the post test and the researcher found that the methods of the training program have a clear effect in the acquisition of the skill of the synoptic formation in the technical supervisors. Through the results, the researcher came up with a set of recommendations and proposals.